Questioning qualitative inquiry critical essays - Hammersley, Martyn (Los Angeles, [Calif.] ; London : SAGE, 2008)
Discussing 50 years of change in qualitative social research Martin Hammersley argues that the move away from natural science as a model for social inquiry involves a rejection of key principles that are essential from any commitment to research.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social sciences -- Research -- Methodology; Qualitative research